Inhibition of Apoptosis Reduces Diploidization of Haploid Mouse Embryonic Stem Cells during Differentiation - Zhang, Wenhao (Stem Cell Reports, 2020)
Phenotypes of haploid embryonic stem cells (haESCs) are dominant for recessive traits in mice. However, one major obstacle to their use is self-diploidization in daily culture. Although haESCs maintain haploidy well by deleting p53, whether they can sustain haploidy in differentiated status and the mechanism behind it remain unknown. To address this, we induced p53-deficient haESCs into multiple differentiated lineages maintain haploid status in vitro. Haploid cells also remained in chimeric embryos and teratomas arising from p53-null haESCs. Transcriptome analysis revealed that apoptosis genes were downregulated in p53-null haESCs compared with that in wild-type haESCs. Finally, we knocked out p73, another apoptosis-related gene, and observed stabilization of haploidy in haESCs. These results indicated that the main mechanism of diploidization was apoptosis-related gene-triggered cell death in haploid cell cultures. Thus, we can derive haploid somatic cells by manipulating the apoptosis gene, facilitating genetic screens of lineage-specific development.